ACTIVITIES SWIMMING AND MOTOR ABILITY CHILDREN AGES EARLY - Taufik Rihatno; Sri Nuraini; Yufiarti Yufiarti; Ahmad Syukri Sitorus (Sriwijaya University Learning and Education International Conference, 2018)
This research aim to test differences motor abilities rude child early age who follow swimming activities at school. Method research survey in 148 students. Collection uses observation of children's motor skills in PAUD. Results research concludes that there are differences in the ability of rough motives of children with the ability child motorics. Implications that facilities in PAUD institutions need to be equipped with swimming pool. Parental participation plays a role important in motor development.